Detection of autoreactive CD4 T cells using major histocompatibility complex class II dextramers - Massilamany, Chandirasegaran (BioMed Central, 2011)
BACKGROUND: Tetramers are useful tools to enumerate the frequencies of antigen-specific T cells. However, unlike CD8 T cells, CD4 T cells - especially self-reactive cells - are challenging to detect with major histocompatibility complex (MHC) class II tetramers because of low frequencies and low affinities of their T cell receptors to MHC-peptide complexes. Here, we report the use of fluorescent multimers, designated MHC dextramers that contain a large number of peptide-MHC complexes per reagent. RESULTS: The utility of MHC dextramers was evaluated in three autoimmune disease models: 1) proteolipid protein (PLP) 139-151-induced experimental autoimmune encephalomyelitis in SJL/J (H-2(s)) mice; 2) myelin oligodendrocyte glycoprotein (MOG) 35-55-induced experimental autoimmune encephalomyelitis in C57Bl/6 (H-2(b)) mice; and 3) cardiac myosin heavy chain (Myhc)-α 334-352-induced experimental autoimmune myocarditis in A/J (H-2(a)) mice. Flow cytometrically, we demonstrate that IA(s)/PLP 139-151, IA(b)/MOG 35-55 and IA(k)/Myhc-α 334-352 dextramers detect the antigen-sensitized cells with specificity, and with a detection sensitivity significantly higher than that achieved with conventional tetramers. Furthermore, we show that binding of dextramers, but not tetramers, is less dependent on the activation status of cells, permitting enumeration of antigen-specific cells ex vivo. CONCLUSIONS: The data suggest that MHC dextramers are useful tools to track the generation and functionalities of self-reactive CD4 cells in various experimental systems.